Security standardisation research : Second International Conference, SSR 2015, Tokyo, Japan, December 15-16, 2015 proceedings /: Second International Conference, SSR 2015, Tokyo, Japan, December 15-16, 2015 proceedings. (2016) - Unknown
No abstract available